Actualization of Students from the Perspective of Imam Al-Ghazali - Helend Priscilla; Qanita Putri Najiyah; Moh. Faizin (Al-Ard: Journal of Education, 2025)
This article explores Al-Ghazali's views on student development in Islamic education, from the basic concept of students as spiritual beings with a natural disposition towards goodness, the importance of ethics or manners in connecting knowledge with teachers, the formation of a holistic character that unites spiritual, intellectual, moral, social, and physical aspects, plus the role of teachers as moral role models. In essence, education today is often fragmented, neglecting the spiritual and ethical dimensions, thus causing a serious moral crisis. To resolve this, I conducted a qualitative analysis of Al-Ghazali's writings, such as Ihya Ulum al-Din, combined with current educational theories and empirical studies. An interesting finding is that Al-Ghazali's framework truly encourages balanced development, with a focus on sincere intentions, humility, and social responsibility, which ultimately leads students to the level of insan kamil or whole human beings. This approach has been shown to increase student motivation, resilience, and ethics, as evidenced in Islamic schools today. In conclusion, Al-Ghazali's ideas are like a panacea for reforming education, helping us deal with issues such as secularization and digital loneliness in a more humane way.